2021
DOI: 10.22219/jrak.v11i2.16855
|View full text |Cite
|
Sign up to set email alerts
|

The Covid-19, Policy And Capital Market: Empirical Evidence From Indonesia

Abstract: This paper aims to examine the impact of Covid-19 on the Indonesian capital market. Second, we test whether any policy from regulators could mitigate its effects. By using daily time-series data from January to July, we propose the simplest regression model (ordinary least squares) to test its effect. We also conducted some robustness with various sectors and splitting samples to make sure that our findings are robust and consistent. We find that Covid-19 (proxied by new cases, cumulative cases, new deaths, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Other than sentiment, studies on the impact of COVID-19 on the financial markets showed that there is a negative relationship between market performance and the number of COVID-19 cases and/or deaths (Al-Awadhi et al, 2020;Ashraf, 2020). In Indonesia, Retnoningsih and Naufa (2021) stated that the total accumulation of COVID-19 cases had a negative impact on the Indonesian stock market. The Indonesian stock market experienced difficulty as a result of this.…”
Section: H1mentioning
confidence: 99%
“…Other than sentiment, studies on the impact of COVID-19 on the financial markets showed that there is a negative relationship between market performance and the number of COVID-19 cases and/or deaths (Al-Awadhi et al, 2020;Ashraf, 2020). In Indonesia, Retnoningsih and Naufa (2021) stated that the total accumulation of COVID-19 cases had a negative impact on the Indonesian stock market. The Indonesian stock market experienced difficulty as a result of this.…”
Section: H1mentioning
confidence: 99%